Adoption of Sustainable Development Goals and Financial Performance of Banks - Saba Iqbal; Safia Nosheen (Indonesian Journal of Sustainability Accounting and Management, 2023)
This paper aims to find out the impact of the adoption of sustainable development goals on the performance of banks in the Asia Pacific region. The major hypothesis of this work assumes that banks adopting sustainable development goals get high financial performance. To measure the SDGs, an ESE index is designed which includes 21 indicators of SDGs. Regression analysis and GMM technique have been used to analyze the impact of the ESE index on the profitability of banks. A separate analysis of economic, social, and environmental indicators has also been done. The findings show that the adoption of SDGs has a positive and significant impact on the financial performance of the banks. This analysis has the following important contributions. First, it gives an insight into the banking sector that the adoption of SDGs is important for increasing profits in the long run. Second, it signals that banks should concentrate on economic, social, and environmental performance also to make this earth a worthy place to live in. This study has novelty in designing the ESE index based on 21 indicators of SDG’s set by the UN’s statistical division.